Immunogenicity and safety of a fourth COVID-19 vaccination in rituximab-treated patients: an open-label extension study. Issue 12 (17th August 2022) - Mrak, Daniel; Simader, Elisabeth; Sieghart, Daniela; Mandl, Peter; Radner, Helga; Perkmann, Thomas; Haslacher, Helmuth; Mayer, Margareta; Koblischke, Maximilian; Hofer, Philipp; Göschl, Lisa; Kartnig, Felix; et al.
Abstract : Objectives: Patients under rituximab therapy are at high risk for a severe COVID-19 disease course. Humoral immune responses to SARS-CoV-2 vaccination are vastly diminished in B-cell-depleted patients, even after a third vaccine dose. However, it remains unclear whether these patients benefit from a fourth vaccination and whether continued rituximab therapy affects antibody development. Methods: In this open-label extension trial, 37 rituximab-treated patients who received a third dose with either a vector or mRNA-based vaccine were vaccinated a fourth time with an mRNA-based vaccine (mRNA-1273 or BNT162b2). Key endpoints included the humoral and cellular immune response as well as safety after a fourth vaccination. Results: The number of patients who seroconverted increased from 12/36 (33%) to 21/36 (58%) following the fourth COVID-19 vaccination. In patients with detectable antibodies to the spike protein's receptor-binding domain (median: 8.0 binding antibody units (BAU)/mL (quartiles: 0.4; 13.8)), elevated levels were observed after the fourth vaccination (134.0 BAU/mL (quartiles: 25.5; 1026.0)). Seroconversion and antibody increase were strongly diminished in patients who received rituximab treatment between the third and the fourth vaccination. The cellular immune response declined 12 weeks after the third vaccination, but could only be slightly enhanced by a fourth vaccination. No unexpected safety signals were detected, one serious adverse event not related to vaccination occurred. Conclusions: A fourth vaccine dose is immunogenic in a fraction of rituximab-treated patients. Continuation of rituximab treatment reduced humoral immune response, suggesting that rituximab affects a second booster vaccination. It might therefore be considered to postpone rituximab treatment in clinically stable patients. Trial registration number: 2021-002348-57.